Innovation Technology of Literature Education at School: Active and Systematical Approach (Филологический класс, 2014)
This article is the first one out of upcoming three articles in total. The article reviews the fundamental basis of perception of literature text by scholars in a sense of active and systematical approach towards contemporary literature educational process.